Women’s Reproductive Health in India: Connecting Government Policies and Programmes with NFHS 5 Data - Nanda, Bijayalaxmi; Ray, Nupur; Mani, Shambhavi (Indian Journal of Community Health, 2025)
Background: Women's reproductive health is an integral part of their overall well-being, and India has made considerable progress in improving reproductive health services. Despite these efforts, persistent issues such as spatially heterogeneous policy outcomes, especially in remote and marginalized areas, remain. Objectives: This research intends to study assess the current state of women’s reproductive health in India, with a focus on contemporary policies and socio-economic differentials. Methods: The study employs a policy review and secondary data analysis method. The data analysed is from NFHS-5 (National Family Health Survey), which provides a comprehensive national representation. Key indicators analysed include maternal health, fertility rate, anaemia, family planning, and gender-based violence to analyse women’s reproductive health. Findings: It is suggested that while government policies have improved education, awareness, and gender equality, certain challenges persist. Notably, anaemia among women aged 15 to 49 increased from 53% in 2015–16 to 57% in 2019–21. Conclusion: It has been noted that initiatives of the government have led to improvement on ground level on fertility behaviour and continuum of care of mother and infants. However, nutritional security for women requires specific attention of the state and society. A community health approach which is sensitive and participatory is recommended for the same.